Students' Appreciation of Indonesian Language Learning During Online - Pratikno, Heru; Atsani Wulansari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
In its development, Indonesian has played a central role in the world of education in the country, from basic education to higher education. As proof, Indonesian is used as the language of instruction in learning. In addition, Indonesian functions as a tool for developing science and technology. With the presence of such a language, it can actually become a strong capital in moving towards an even greater Indonesian nation. However, what does that mean if the users, especially the younger generation, namely students, don't care about their own language. This can be reflected when they take Indonesian language courses online. Therefore, the aim of this research is to explain what problems students have in learning Indonesian at Islamic universities. Apart from that, the author tries to find the best solution to solve this problem so that it is resolved. The method used in this paper is direct observation of the behavior of students studying Indonesian online. The hypothesis is that there is a strong correlation between lecturers and students to create a comfortable Indonesian language lecture atmosphere.